Ultrastructure of mitochondria and damage to small blood vessels in siblings with the same mutation in the NOTCH 3 and coexisting diseases - Felczak, Paulina; Cudna, Agnieszka; Błażejewska-Hyżorek, Beata; Buczek, Julia; Kurkowska-Jastrzębska, Iwona; Stępień, Tomasz; Acewicz, Albert; Wierzba-Bobrowicz, Teresa (Polish Journal of Pathology, 2021)
We performed ultrastructural studies of mitochondria and evaluated the appearance of small blood vessels of three middle-aged siblings affected by the same mutation in the NOTCH3 gene, causing CADASIL. CADASIL pathognomonic features include granular osmiophilic material (GOM), which we observed. GOMs were located in damaged and thickened basement membranes (BM) of capillaries and arterioles. Our patients were also burdened by type II diabetes (first patient), impaired glucose metabolism (second patient), and hypertension (third patient). The ultrastructure of the capillaries in the first and second patients differed from the third patient. In diabetes/impaired glucose metabolism patients (first and second patients), we observed: pathologies of mitochondria in damaged endothelium and pericytes of capillaries; extremely thickened (BM) with visible remains of vascular cells; well-preserved GOMs anchored in the rebuilt capillary extracellular matrix. We identified degenerated or vestigial small blood vessels of skeletal muscles in the first patient. The capillary damage in the third patient (with hypertension) was milder compared to the diabetes/impaired glucose metabolism patients. We conclude that in patients with a mutation in the NOTCH3 gene, the co-occurrence of diseases such as type II diabetes/impaired glucose metabolism can cause a multiplication the damages to small blood vessels by modifying/masking the pathogenesis of CADASIL.